Comida ritual em festas de Tambor de Mina no Maranhão (Ritual food in Maranhão’s Tambor De Mina festivities) - DOI: 10.5752/P.2175-5841.2011v9n21p242 - Ferretti, Sérgio Figueiredo (Horizonte, 2011)
Tambor de Mina is the name of the Afro-Brazilian religion in Maranhão and Amazon established in São Luís (capital of Maranhão state) since the mid-nineteenth century. There are two matrix-houses founded by Africans: Casa das Minas Jeje, a Dahomean origin house and Casa de Nagô, originally Yoruba and from which most of the Tambor de Mina's houses come from. It is a very ritualized and discrete religion, involved in secrets and mysteries whose mythology is not frequently commented upon and its rituals are highly developed. Afro-Brazilian religions are characterized by the performance of parties with trance, dance and food which attract many participants. Food is enough to be offered to everyone and have the remains distributed. The abundance of food during the bigger festivities constitutes a prestige element to the houses. According to Mauss, sacrifice is an obligation that establishes communication between sacred and profane. The preparation and consumption of holy feast food allow us to know aspects of syncretism and symbolisms in rituals